THE EFFECTIVENESS OF BEHAVIOR THERAPY WITH A POSITIVE REINFORCEMENT APPROACH TO ACADEMIC PROCRASTINATION OF DEAF STUDENTS - Irna Afifah Amanda Sari; Mei Dwi Yanti; Annisa Rizqi Wijaya; Muhammad Aziz Gibran; Wawan Nopriansa; Diwie Asbania; Siti Saluna Nurhaliza; Elan Gunzales; Junita Ibrahim; Dinda Azzahra Nastasya; Annisa Fikri Sovia Ahmad; Septiane Dwi Puspitarani; Dewa Bayu Hermanto (CV. Doki Course and Training, 2023)
The reaserch aims to find out the effectiveness of behavior therapy with a positive reinforcement approach on reducing academic procrastination of deaf students at SMPLB Negeri Pembina Palembang. The research method is a quantitative pre-experimental research design with a one group pre-test post-test design. The subjects of this research were determined using a purposive sampling technique (N = 15) all of whom were deaf youth at SMPLB Negeri Pembina Palembang. To measure the level of academic procrastination used procrastination scale by Qomariyah (2016). The data analysis technique used the Paired Sample T-Test through SPSS. Based on the results of the pretest and posttest, the value of p = 0.002 (p <0.05) was obtained. Thus, it can be concluded that behavior therapy with a positive reinforcement approach has an effect on reducing academic procrastination of deaf students at SMPLB Negeri Pembina Palembang.